Developmental psychology and early childhood education : a guide for students and practitioners - Whitebread, David, 1948- (SAGE, 2012)
"The importance of high quality early childhood education is now universally recognized, and this quality crucially depends upon the practitioners who work with our young children, and their deep understanding of how children develop and learn. This book makes a vital contribution to this understanding, providing authoritative reviews of key areas of research in developmental psychology, and demonstrating how these can inform practice in early years educational settings." -- Publisher's information.